Are all migrants really worse off in urban labour markets? New empirical evidence from China - Jason Gagnon; Theodora Xenogiani; Chunbing Xing (Institute for the Study of Labor (IZA), 2011)
The rapid and massive increase of rural-to-urban migration in China has drawn attention to the welfare of migrant workers, particularly to their working conditions and pay. This paper uses data from a random draw of the 2005 Chinese national census survey to investigate discrimination in urban labour markets against rural migrants, by comparing their earnings and the sector (formal vs. informal) they work in with those of urban residents and urban migrants. Exploiting differences in their status in the Chinese residential registration system (hukou) we find no earnings discrimination against rural migrants compared with urban residents, contrary to popular belief. In contrast, we find that urban migrants in fact gain a large wage premium by migrating. However, both rural and urban migrants are found to be discriminated out of the formal sector, working in informal jobs and lacking adequate social protection.
urn:nbn:de:101:1-201203016593
Keywords: O15; R23; J24; J71; 330; migration; China; discrimination; informal employment